Development of a recovery monitoring prediction model for female and male elite athletes: a longitudinal study - Engler, L.; Trotter, C.; Eggenberger, P. (Current Issues in Sport Science, 2026)
Introduction and purpose: Overtraining syndrome (OTS) might occur in athletes experiencing extreme physical and mental stress over a longer period of time without adequate recovery (Meeusen et al., 2013). A decrease in sports performance and chronic fatigue are the most frequent symptoms (Carrard et al., 2021; Meeusen et al., 2013). Reliable diagnostic and monitoring tools are lacking but are strongly needed due to the high prevalence of OTS of 5 to 64 % (depending on definition and sample) and its potential reducing risk of injury (Meeusen et al., 2013). We aimed to develop novel sex-specific, non-invasive and multiparametric recovery monitoring models.